(untitled) (Research, Society and Development, 2023)
Introduction: During the SARS-CoV-2 pandemic, social distancing was a useful but impractical measure for many people. Some professional categories faced particular challenges, such as bus conductors working in environments with poor air circulation and garbage collectors exposed to contaminated surfaces. However, increased aerobic capacity may have provided a protective factor for the latter group. Objectives: analyze the frequency of SARS-CoV-2 infection and physical activity levels of workers, and compare their peak expiratory flow rate (PEFR) after COVID-19. Methods: the study used a retrospective analytical cross-sectional observational with 52 workers divided into three groups: urban public transport professionals (N=18), urban cleaning workers (N=21), and civil servants who worked remotely (N=13). Physical activity levels were measured using the long version of the International Physical Activity Questionnaire, and PEFR was measured using a Peak Flow. Results: SARS-CoV-2 infection rate of 19% was observed for urban cleaning professionals, 44% for bus conductors, and 61.5% for public servants, demonstrating a significant difference in the probability of being infected with SARS-CoV-2 and developing COVID-19 among these groups. Two workers reported having obstructive pulmonary diseases, although three workers had PEFR values below 80%, indicating a possible presence of these diseases. Conclusion: there is a significant difference in the probability of SARS-CoV-2 infection and developing COVID-19 among each group, which can not be explained by differences in their physical activity levels.